Effect of the Combination of Everolimus and Mesenchymal Stromal Cells on Regulatory T Cells Levels and in a Liver Transplant Rejection Model in Rats - Vandermeulen, Morgan; Erpicum, Pauline; Bletard, Noella; Poma, Laurence; Jouret, François; Detry, Olivier (Frontiers in Immunology, 2022)
Introduction: Mesenchymal stromal cells (MSCs) have particular properties that are of interest in organ transplantation, including the expansion of regulatory T cells (Tregs), a key factor in transplant tolerance induction. However, the most effective immunosuppressive drug to associate with MSCs has yet to be defined. Additionally, the impact of the association of everolimus with MSCs on Treg expansion, and on the induction of liver graft tolerance, has never been studied. The aim of this study was to evaluate the effects of MSCs in combination, or not, with everolimus on Treg expansion and additionally in a model of rejection after liver transplantation (LT) in the rat. Methods: Firstly, 24 Lewis rats were assigned to 4 groups (n=6 in each group) receiving intravenous MSCs or saline injection at day (D)9 with/without subcutaneous everolimus from D0 to D14. Analysis of circulating Tregs was performed at D0, D14 and D28. In a second set of experiment, 30 Lewis rats were randomized in 3 groups 48hours after LT with a Dark Agouti rat liver: everolimus (subcutaneous for 14 days), MSCs (intravenous injection at post-operative day 2 and 9), or both everolimus and MSCs. Rejection of the liver graft was assessed by liver tests, histology and survival. Results: Individually, MSC infusion and everolimus promoted Treg expansion in rats, and everolimus had no negative impact on Treg expansion in combination with MSCs. However, in the LT model, injections of MSCs two and nine days following LT were not effective at preventing acute rejection, and the combination of MSCs with everolimus failed to show any synergistic effect when compared to everolimus alone. Conclusion: Everolimus may be used in association with MSCs. However, in our model of LT in the rat, post-transplant MSC injections did not prevent acute rejection, and the association of MSCs with everolimus did not show any synergistic effect.